Telling great data stories online - Mackinlay, Jock D.; Safari eBooks; O'Reilly Strata making data work conference ([S.l.] : O'Reilly Media, 2011)
"Interactive visualizations have become the new media for telling stories online. This session will focus on going from a good visualization to a great visualization by focusing on organization, user interface, and formatting. You should expect to leave this session confident in your ability to consistently create excellent interactive visuals"--Resource description page.
Presenter, Jock Mackinlay.
Recorded at the O'Reilly strata making data work conference, held at Santa Clara, Calif., Feb. 1-3, 2011.
Keywords: Information visualization; Interactive multimedia; Computer graphics; Electronic books